Optimization of culture conditions for Gardnerella vaginalis biofilms formation - Machado, D. (2015)
Bacterial vaginosis is the leading vaginal disorder in women in reproductive age. Although bacterial vaginosis is related with presence of a biofilm composed predominantly by Gardnerella vaginalis, there has not been detailed information addressing the environmental conditions influence in the biofilm formation of this bacterial species. Here, we evaluated the influence of some common culture conditions on G. vaginalis biofilm formation, namely inoculum concentration, incubation period, feeding conditions and culture medium composition. Our results showed that culture conditions strongly influenced G. vaginalis biofilm formation and that biofilm formation was enhanced when starting the culture with a higher inoculum, using a fed-batch system and supplementing the growth medium with maltose.